Applying non-linear dynamics in the Singapore stock market using Chaos theory - Foo, Onn Siew (2014)
The question of whether the Stock Exchange of Singapore (SES) is weak-form efficient under the Efficient Market Hypothesis (EMH) has been a topic of much debate. Although various tests have been conducted to verify its efficiency, they have yielded inconclusive and mixed results. The problem may lie in the fault of the models used and their simplifying assumptions. All the current tests for weak form efficiency are based on the linear model, which we will show may be invalid to be used for analysing the capital markets, since capital markets are non-linear in nature.